2010
DOI: 10.1111/j.1550-7408.2010.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

ADaphniaParasite (Caullerya mesnili) Constitutes a New Member of the Ichthyosporea, a Group of Protists near the Animal–Fungi Divergence

Abstract: ABSTRACT. Caullerya mesnili is a protozoan endoparasite in the gut epithelium of Daphnia, which causes regular epidemics in lakes throughout Europe. Its classification has remained unchanged for over a century, leaving it placed with the Haplosporidia, despite speculation that this position is incorrect. The difficulty in classifying C. mesnili stems from its few known morphological and ecological characteristics, as well as a lack of genetic markers. Here we sequenced the nuclear small subunit (SSU) and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(90 citation statements)
references
References 30 publications
(51 reference statements)
3
87
0
Order By: Relevance
“…The number of taxa in the group has increased from 12 species (reviewed by Mendoza et al 2002) to the present number of over 40, although about half of these are phylotypes. Several additional species including parasites of amphibians, marine invertebrates, beetles and water fleas have been described (Feldman et al 2005;Marshall et al 2008;Lohr et al 2010;Marshall & Berbee 2011;Lord et al 2012). Many taxa in the Eccrinales and Amoebidiales inhabiting the gut or on the exoskeleton of arthropods, which were once placed in the fungal class Trichomycetes (Zygomycotina), have been recognized as Mesomycetozoean protists following phylogenetic analysis (Benny & O'Donnel, 2000;Mendoza et al 2002;Cafaro 2005).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The number of taxa in the group has increased from 12 species (reviewed by Mendoza et al 2002) to the present number of over 40, although about half of these are phylotypes. Several additional species including parasites of amphibians, marine invertebrates, beetles and water fleas have been described (Feldman et al 2005;Marshall et al 2008;Lohr et al 2010;Marshall & Berbee 2011;Lord et al 2012). Many taxa in the Eccrinales and Amoebidiales inhabiting the gut or on the exoskeleton of arthropods, which were once placed in the fungal class Trichomycetes (Zygomycotina), have been recognized as Mesomycetozoean protists following phylogenetic analysis (Benny & O'Donnel, 2000;Mendoza et al 2002;Cafaro 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Recent detailed morphological and ultrastructural studies of cultivated species (Marshall et al 2008;Marshall & Berbee 2011), studies of species in association with the host (Gonz alez-Hern andez et al 2010; Lohr et al 2010;Hernandez Roa & Cafaro 2012;Lord et al 2012) and ecological surveys with environmental sampling (Stougaard et al 2002;Savin et al 2004;Takishita et al 2005Takishita et al , 2006, have enhanced our knowledge of the ecology of the Mesomycetozoea. In this paper we review the general biology of the Mesomycetozoea with particular emphasis on ecological information accumulated during the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…For C. mesnili the number of visible spore clusters was recorded every second day from when spores were first visible. As C. mesnili spores are released from the gut (Lohr et al 2010), the number of spore clusters observed every second day over the course of the infection was summed and used as an estimate of life-time spore production. For Metschnikowia sp., the number of both mature and immature spores was determined after host death : each individual was homogenized in 0 .…”
Section: Recorded Parametersmentioning
confidence: 99%
“…In this study, we addressed infections of a single Daphnia genotype by 2 sympatric lake parasites (a single genotype of each) ; an intestinal protozoan Caullerya mesnili (class Ichthyosporea, Lohr et al 2010) and a haemolymph fungus Metschnikowia sp. (family Hemiascomycetes, Wolinska et al 2009).…”
mentioning
confidence: 99%
“…The biological formation of Y-shaped cell junctions requires flexible cell membranes and cell-cell adhesion (14), an important step toward complex multicellularity (15). Third, cell cleavage in Parapandorina (as in modern animals) follows a 2 n sequence, whereas cytokinesis in most protists, including mesomycetozoeans, does not follow a 2 n sequence because it commonly involves multinucleate stages (16)(17)(18).…”
mentioning
confidence: 99%